قواعد أصول الحديث في رسالة الإمام الشافعي محمد بن إدريس رحمه الله تعالى: Fundamentals of the Science of Hadith in Ar-Risālah (the Epistle) by Imam Al-Shāfi’ī - Yasser Mohammad Nouri Aldeirshawi (Maʿālim al-Qurʾān wa al-Sunnah, 2020)
This research is an inductive analytical study on the fundamentals of the science of Hadith extrapolated by Imam Al-Shāfi’ī (May Allah have mercy on him) in his book Ar-Risālah (The Epistle) along with the discussion of later scholars. In this research, I identified all these principles and theories that are related to the science of Hadith that were discussed in the book. In addition, I made a thorough study on the scholars’ position with their views, opinions and understandings to them. In the end, I came across some findings, most important among them is that, Imam Al-Shāfi’ī was the first to establish the fundamentals theories of the science of Hadith, as he was the first to coined its terminologies, and discussed the theories in such a way never preceded by any scholar. These were later, the subsequent scholars relied upon them in their writings.